2015
DOI: 10.2500/ajra.2015.29.4246
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Nasal Irrigation as an Adjuvant Therapy after Functional Endoscopic Sinus Surgery

Abstract: Our study showed that nasal irrigation with 100 μg/mL of AMB did not confer a greater benefit than that of NS solution nasal irrigation in post-FESS care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…These investigators intriguingly demonstrated that subjects with E-CRS (and not the healthy controls) had circulating T effector lymphocytes that secreted IL-5 in response to Alternaria 56 . Subsequently, this line of research has been dismissed because of the overwhelming evidence that sinus irrigation with anti-fungal antibiotics fails to produce clinical benefit 57, 58 . However, that seems an unfair argument against this as a mechanism, as anti-fungals are consistently ineffective in AFRS despite universal acceptance that it is a fungally-mediated disease.…”
Section: Introductionmentioning
confidence: 99%
“…These investigators intriguingly demonstrated that subjects with E-CRS (and not the healthy controls) had circulating T effector lymphocytes that secreted IL-5 in response to Alternaria 56 . Subsequently, this line of research has been dismissed because of the overwhelming evidence that sinus irrigation with anti-fungal antibiotics fails to produce clinical benefit 57, 58 . However, that seems an unfair argument against this as a mechanism, as anti-fungals are consistently ineffective in AFRS despite universal acceptance that it is a fungally-mediated disease.…”
Section: Introductionmentioning
confidence: 99%
“…The lower concentration of 100 μg/mL used in our previous study is commonly recommended, while other studies proposed the use of higher concentrations . Our earlier study of post‐FESS care showed that nasal irrigation with 100 μg/mL concentration of AMB did not provide benefits over saline controls . In the present study, we adopted the concentration of 200 μg/mL.…”
Section: Discussionmentioning
confidence: 91%
“…Nasal irrigation is a common adjuvant treatment after functional endoscopic sinus surgery (FESS). In our previous study, a concentration of 100 μg/mL of AMB at a daily dose of 20 mg was used for the irrigation after FESS, and we found no benefits over the control irrigation with saline . Whether higher AMB concentration would improve the benefit of post‐FESS care is uncertain.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…30 Subsequently, enthusiasm for this line of research has been diminished due to overwhelming evidence that sinus irrigation with antifungal agents fail to produce clinical benefit. [31][32][33] Our assumption going into this study was that the actions of azole antifungals would be to prevent de novo differentiation of naive T cells. Because this demonstrably is not its mechanism of action, the alternative explanation, in regard to potential actions on effector T cells, would be to inhibit the function, proliferation, or survival of established effector T cells.…”
Section: Figure 2 Proliferation Of Naive T Cells Stimulated With Itrmentioning
confidence: 99%